Respuesta :
Answer:
Simplified form of [tex]\frac{\frac{X^2+7X+10}{X-2} }{\frac{X^2-25}{X-8} } = \frac{4(X+2)}{(X-5)}[/tex]
Step-by-step explanation:
Here, the given expression is
[tex]\frac{\frac{X^2+7X+10}{X-2} }{\frac{X^2-25}{X-8} } = \frac{P(X)}{Q(X)} \\\implies P(X) = {\frac{X^2+7X+10}{X-2} , Q(X) = \frac{X^2-25}{4X-8}[/tex]
Now, using the Algebraic Identities:
[tex](a^2 - b^2) = (a+b)(a-b)[/tex]
Simplify P(X) and Q(X) separably:
[tex]P(X) = \frac{X^2+7X+10}{X-2} = \frac{X^2+5X + 2X+10}{X-2} \\\implies P(X) = {\frac{X(X + 5) +2(X+5)}{X-2} \\= P(X) = {\frac{(X+ 5)(X+2)}{X-2} \\\\\implies P(X) = {\frac{(X+ 5)(X+2)}{X-2}[/tex]
Similarly, Q(X) = [tex]\frac{X^2-25}{4X-8} = \frac{(X-5)(X+5)}{4X-8} \\\implies Q(X) = \frac{(X-5)(X+5)}{4(X-2)}[/tex]
hence, the given fraction is simplified to
[tex]\frac{P(X)}{Q(X)} = \frac{\frac{(X+ 5)(X+2)}{(X-2)} }{\frac{(X-5)(X+5)}{4(X-2)} }[/tex]
[tex]\implies \frac{P(X)}{Q(X)} = \frac{\frac{(X+ 5)(X+2)}{(X-2)} }{\frac{(X-5)(X+5)}{4(X-2)} } ={\frac{(X+ 5)(X+2)}{(X-2)} } \times {\frac{ 4(X-2)}{(X-5)(X+5)} = \frac{4(X+2)}{(X-5)}[/tex]
Hence, the simplified form of [tex]\frac{\frac{X^2+7X+10}{X-2} }{\frac{X^2-25}{X-8} } = \frac{4(X+2)}{(X-5)}[/tex]
Answer: 4(x + 2) / x - 5
Step-by-step explanation: A P E X (the parenthesis confused the heck out of me)